Early prediction of sarcoidosis prognosis with HLA typing: A 5 year follow-up study - Ozyilmaz, Ezgi; Ozturk, Ozlem Goruroglu; Durmaz, Ali; Hasan, Orhan Othman; Guzelbaba, Bugra; Seydaoglu, Gulsah; Kuleci, Sedat; Hanta, Ismail; Erken, Eren; Kocabas, Ali (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: A wide range of HLA-DR alleles have been associated with sarcoidosis either in terms of disease phenotype or extra pulmonary involvement, however the effect on non-resolution in different ethnic groups is not fully understood. The aim of this study was to investigate whether disease characterics and HLA-DRB1 alleles may early reflect non resolution in sarcoidosis. Methods: 91 patients who were diagnosed in Cukurova University Faculty of Medicine Department of Chest Diseases between 1993-2012 and were followed up until June 2017 were included in the study. All patients underwent HLA analysis by the Sequence Specific Oligonucleotide Prob (SSOP) method. Fifteen of them were excluded from the study group due to lost of follow-up (n=6) and not yet passed 5 years since diagnosis (n=9). Complete resolution at 5th year was defined according to the predefined standard criteria (ACCESS). Results: The resolution rate was 51.3%. The HLA-DRB1*14 allele was significantly higher in patients without resolution (11.8 vs 1.3%)(p=0.006). According to multivariate logistic regression analysis the independent risk factors of non resolution were female gender (OR: 12.6; 95%CI: 2.1-74.9, p=0.005), HLA DRB1*14 allele (OR:51.9; 95%CI: 3.6-735.8, p=0.000), baseline TLCO